2004
DOI: 10.1111/j.1365-2567.2004.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional heterogeneity of porcine blood monocytes and its relation with maturation

Abstract: Summary Swine monocytes constitute a heterogeneous population of cells which can be divided into four subsets based on the expression of SWC3, CD14, CD163 and swine leucocyte antigen (SLA) DR markers. These subsets appear to represent different maturation stages in a pathway along which these cells up‐regulate the expression of SLA DR and CD163 antigens and reduce that of CD14. Differences in the expression of adhesion and costimulatory molecules are also patent, with a progressive increase in the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 54 publications
1
59
0
4
Order By: Relevance
“…CD14 lo , CD163 hi monocytes also expressed the highest levels of the swine leukocyte Ag (SLA) class II genes (SLA-DRB1, SLA-DQA, SLA-DQB1, SLA-DRA, SLA-DRB1, SLA-DRB2), suggesting a role in Ag processing and presentation (42). A similar role in MHC processing has been described for human ' (42, 43).…”
Section: Discussionmentioning
confidence: 74%
“…CD14 lo , CD163 hi monocytes also expressed the highest levels of the swine leukocyte Ag (SLA) class II genes (SLA-DRB1, SLA-DQA, SLA-DQB1, SLA-DRA, SLA-DRB1, SLA-DRB2), suggesting a role in Ag processing and presentation (42). A similar role in MHC processing has been described for human ' (42, 43).…”
Section: Discussionmentioning
confidence: 74%
“…+ monocytes produce more TNF-, express high levels of adhesion molecules and are better at presenting antigens to T cells when compared to CD163 − monocytes [48]. In addition, the DC derived from CD163 + monocytes, express higher levels of MHC class II and CD80/86 and are more efficient antigen presenting cells [49].…”
Section: Cd163mentioning
confidence: 99%
“…CD163 is highly expressed in these mature tissue macrophages, whereas its expression level is modest in monocytes (65). This is important because it distinguishes CD163 as a differentiation marker of the macrophage lineage with increased expression along the macrophage differentiation pathway (65,66). Studies have demonstrated CD163-expressing macrophages in a number of diseases associated with inflammation, including arthritic joints (67), tumors (68) and atherosclerosis (69).…”
Section: Cd163: the Second Definite Receptormentioning
confidence: 99%